Nature's choice? a study of the displacement of incumbents in elections - Canen, Nathan Joseph (2013)
How do economic shocks affect the behaviour of elections in democracies? Using U.S. Congress electoral data, I test whether sudden shocks affect unequally incumbent par- ties and opponents. This is identified through, among other procedures, a regression discontinuity design. I consider possible theoretical channels for this effect, where cit- izens cannot perfectly observe whether their lack of public goods is due to an adverse shock, or due to private consumption by a politician. I find that, with observable shocks close to the election, there is no effect. Empirical evidence is consistent with the theory.